Everyday Life Information Seeking of International Students in Taiwan - Bobie Hartanto; Zunvindri Zunvindri (Communicology: Jurnal Ilmu Komunikasi, 2016)
The increasing number of international student enrolled all around the world that leads to the needs of information problem. Different background, social demography, and general information affect the needs of information of international students. The genre of information to be search on the internet and the use of internet in seeking everyday life information take attention of researcher. The research intended to find interrelation between Social demography and general information toward genre of information chosen. This research questions were answered by conducting survey using questionnaire. Online questionnaire is chosen as the method to collect information from international students who are studying in Taiwan. This study finding released that Internet had been used as a primary medium for seeking information and most of the International students are having tendency to search information related to entertainment compare to other genre of everyday life information. In fact, personal interest information which is having important value got a low interest.Keywords: Everyday life information, Social demography, International Students.